If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + -6)(4x + 9) = 0 Reorder the terms: (-6 + x)(4x + 9) = 0 Reorder the terms: (-6 + x)(9 + 4x) = 0 Multiply (-6 + x) * (9 + 4x) (-6(9 + 4x) + x(9 + 4x)) = 0 ((9 * -6 + 4x * -6) + x(9 + 4x)) = 0 ((-54 + -24x) + x(9 + 4x)) = 0 (-54 + -24x + (9 * x + 4x * x)) = 0 (-54 + -24x + (9x + 4x2)) = 0 Combine like terms: -24x + 9x = -15x (-54 + -15x + 4x2) = 0 Solving -54 + -15x + 4x2 = 0 Solving for variable 'x'. Factor a trinomial. (-9 + -4x)(6 + -1x) = 0Subproblem 1
Set the factor '(-9 + -4x)' equal to zero and attempt to solve: Simplifying -9 + -4x = 0 Solving -9 + -4x = 0 Move all terms containing x to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + -4x = 0 + 9 Combine like terms: -9 + 9 = 0 0 + -4x = 0 + 9 -4x = 0 + 9 Combine like terms: 0 + 9 = 9 -4x = 9 Divide each side by '-4'. x = -2.25 Simplifying x = -2.25Subproblem 2
Set the factor '(6 + -1x)' equal to zero and attempt to solve: Simplifying 6 + -1x = 0 Solving 6 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + -1x = 0 + -6 Combine like terms: 6 + -6 = 0 0 + -1x = 0 + -6 -1x = 0 + -6 Combine like terms: 0 + -6 = -6 -1x = -6 Divide each side by '-1'. x = 6 Simplifying x = 6Solution
x = {-2.25, 6}
| 0.6x+0.3y=3 | | 3(5r-8)=36 | | 8x+7=3x+27 | | 5+1x=56 | | 5y-4+y+20=5y+20-1y | | 9x^2=42x-49 | | 11p-4+p= | | 2t+9=15-t | | 10+3z+z-5= | | -8+4h+1-h= | | 5+9c-10= | | -6k+10-4k= | | 33=46y | | 7b+12+4b= | | x^3-5x^2-4x=0 | | 23x^2-26x=0 | | 21-10t+x+9-2t= | | -3(3p+4)-2(2-14p)=3(9+6p) | | 36x^2-4=0 | | -3(3p-4)-2(2-14p)=3(9+6p) | | -5+x+2x= | | 5-5-5-5-5-5*-6=8xy | | 2p-11=-41+8p | | 11-16-a= | | 2v+3-4v=-1(v+9) | | 2p-24=18+9p | | -15u^2v^2+25u^2v-40uv^2= | | 5x^3+x^2-24x-13=36 | | 3y=-2x+7 | | X*x-121=8 | | 3(-3x-1)=-8(x-1) | | (a+5)-(a+3)= |